(untitled) - Kriz, Josef; Novak, Andrej (Doprava a spoje, 2005)
The centenary anniversary Orwill Wright's flight and introduction biggest aeroplanes in the world is stimulus toward much consideration. Single from they is consideration about influence piston and gas turbine aircraft engine on environment. Be analyze present state and assumes improvements aircraft engines in efficiency, economy and decreasing his unfavorable influence on environment. Case study in noise, fuel burn, emissions and reliability with revolutionary options in more electric and electronic aircraft engine.Accomplishments evolution air transport, to by which development aircraft engine prominently redounded implies comparison growth realized passenger-kilometres performed (PKPs) and growth consumption aviation fuels during 1971 and 2001 according to statistic IEA (International Energy Agency) and ICAO.